Impact of components of metabolic syndrome on the risk of adverse renal outcomes in patients with atrial fibrillation: a nationwide cohort study - Kwon, Soonil; Lee, So-Ryoung; Choi, Eue-Keun; Lee, Seung-Woo; Jung, Jin-Hyung; Han, Kyung-Do; Ahn, Hyo-Jeong; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2023)
The renal effect of metabolic syndrome components is unclear in patients with atrial fibrillation. This study aimed to investigate the association between metabolic syndrome components and incident end-stage renal disease among patients with atrial fibrillation.Methods: A total of 202,434 atrial fibrillation patients without prevalent end-stage renal disease were identified from the National Health Insurance Service database between 2009 and 2016. We defined the metabolic score range from 0 to 5 points such that a patient received every 1 point if the patient met each component listed in the diagnostic criteria of metabolic syndrome. The population was divided into 6 groups: MS0~MS5 for a metabolic score of 0~5, respectively. Multivariate Cox regression analysis was used to estimate the risks of end-stage renal disease.